IS THERE A SOCIOLOGICAL EXPLANATION FOR SUICIDE? - Sapunaru, Raquel Anna; Luiza Mendes de Castro, Ana (Revista Gênero e Interdisciplinaridade, 2022)
The present work discusses the role and importance of sociology, through some views. It also deals with the work of Émile Durkheim, who is considered one of the founding sociologists of this science, as he was the only sociologist to deal with suicide as a social fact and not a medical-physiological phenomenon. Durkheim defines four types of suicide, namely: egoistic, altruistic, anomic and fatalistic. The discussion made here is extensive, covering various aspects of the sociology of suicide, so to speak. Roughly speaking, the objectives of this work are to discuss the issue of suicide from the point of view of sociology and to briefly study the work of the sociologist Émile Durkheim, linked to the issue of suicide.The methods used are bibliographic, with historical and comparative aspects.